2006
DOI: 10.1080/07357900600981307
|View full text |Cite
|
Sign up to set email alerts
|

Response to Neoadjuvant Chemotherapy in Breast Cancer Could be Predictable by Measuring a Novel Serum Apoptosis Product, Caspase-Cleaved Cytokeratin 18: A Prospective Pilot Study

Abstract: The M30-monoclonal antibody recognizes a neo-epitope of cytokeratin 18 which is formed after caspase-cleavage during apoptosis. Caspase-cleaved cytokeratin 18 is released from apoptotic cells into circulation. The aim of this study was to evaluate the relationship between M30-antigen level and chemotherapy response in neoadjuvant treatment of breast cancer. Forty-two patients with invasive breast carcinoma received 4 cycles of anthracycline based neoadjuvant chemotherapy. Serum samples were obtained for assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 29 publications
4
57
1
Order By: Relevance
“…Large clinical studies would allow investigators to evaluate the relationship between caspase-cleaved CK18 fragments and disease risk in patients with cancer, as well as therapeutic responses. CK18 shows considerable promise as an important marker of therapeutic efficacy (66,67,(70)(71)(72). Further, in combination with other markers, the use of CK18 could be an important step toward preselecting patients to determine the most appropriate therapy for their particular disease status.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Large clinical studies would allow investigators to evaluate the relationship between caspase-cleaved CK18 fragments and disease risk in patients with cancer, as well as therapeutic responses. CK18 shows considerable promise as an important marker of therapeutic efficacy (66,67,(70)(71)(72). Further, in combination with other markers, the use of CK18 could be an important step toward preselecting patients to determine the most appropriate therapy for their particular disease status.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, total CK18 showed potential as a prognostic marker in patients with non-small cell lung cancer, whereas caspase-cleaved CK18 had no prognostic value (65). Different investigators have reported encouraging data regarding the potential use of CK18 as a serum biomarker to assess the treatment efficacy of chemotherapy for various carcinomas, including gastrointestinal carcinomas (66,67), breast cancer (71,72), and lung cancer (70).…”
Section: Clinical Applications Of Ck18mentioning
confidence: 99%
See 1 more Smart Citation
“…Its prime utility is in monitoring treatment and in providing early indications on recurrence and tumor progression. Encouraging data have been reported by various groups with regard to the potential use of CK18 as a clinically useful biomarker for monitoring treatment efficacy in cancer patients (24,35,36). We are currently investigating the expression of CK18 in PCa tissues and serum to predict and monitor paclitaxel responsiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Both M30 and M65 assays have now been applied extensively in clinical trials as biomarkers of cell death induced by a variety of different cancer chemotherapeutic agents in a spectrum of different disease types (Biven et al, 2003;Ueno et al, 2003;Kramer et al, 2004Kramer et al, , 2006Demiray et al, 2006;Ulukaya et al, 2007). In some preliminary reports, the M30 assay has been claimed to be both predictive of drug response (Demiray et al, 2006) and prognostic of survival (Ulukaya et al, 2007).…”
Section: Detection Of Ck Expression In the Diagnosis Of Tumorsmentioning
confidence: 99%